The Influence of Distributed Leadership on Effective School The Influence of Distributed Leadership on Effective School Governance and Improved School Performance A Study Governance and Improved School Performance A Study Conducted in Two Private Schools in the UAE - Hassanieh, Rima Al (2020)
The purpose of this research is to identify the impact of Distributed Leadership (DL) on school governance, leading to an improvement in the overall school performance. This study was conducted in two private schools in the UAE. The review of related literature helped to understand the concept of distributed leadership and its impact on governance, school performance, and organizational hierarchy. The data was collected using a mixed method using surveys and interviews. The data was analyzed using descriptive analysis and moderated regression analysis. The conclusion reached was that DL has a positive impact on the relationship between governance and performance. It was also found that DL was being applied in both schools at varying levels, and each had areas that needed improvement. The most important implication was the connection of DL to governance and performance. The findings offer relevant insights for schools studied, as well as for similar schools.